1969
DOI: 10.1037/h0027423
|View full text |Cite
|
Sign up to set email alerts
|

Tactual and visual illusions in the T-shaped figure.

Abstract: A. G, Experiments on sensory-tonic field theory of perception: VII. Effect of asymmetrical extent and starting position of figures on the visual apparent median plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Kunnapas (1955a) and Tedford and Tudor (1969) found a negative HVI with the side-T figure, while Finger and Spelt (1947) and the present study found a small, but positive, HVI with this figure. Several differences in experimental design and stimulus conditions are correlated with the difference.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Kunnapas (1955a) and Tedford and Tudor (1969) found a negative HVI with the side-T figure, while Finger and Spelt (1947) and the present study found a small, but positive, HVI with this figure. Several differences in experimental design and stimulus conditions are correlated with the difference.…”
Section: Resultsmentioning
confidence: 53%
“…He inferred that these results indicated the effects of two illusions in his figures, an overestimation of the vertical line and an overestimation of the dividing line. He suggested that the latter effect was variable, depending upon the point of intersection, and that the two illusions summated in the T and inverted T but opposed one another in the side T. Tedford and Tudor (1969) and Finger and Spelt (1947) also compared the inverted and side-T figures. Both confirmed that the inverted T yielded a greater illusion than the side T. In agreement with Kunnapas, Tedford and Tudor found a reversal of the illusion with the side T (i.e., a greater divided-line illusion), while Finger and SpeIt found a small, but positive, illusion (a greater HVI).…”
Section: New Mexico Institute Ofmining and Technology Socorro New Mmentioning
confidence: 99%
“…In the second experiment, we sought to further examine the impact of relevant factors by rotating the curves 90º to the right. The effect of the positive rotation was to prompt radial scanning of the bases of curves and eliminate most of this forward-and-back arm motion during scanning for the rotated curved lines themselves (see also Künnapas, 1955;Tedford & Tudor, 1969). In vision, rotation of an inverted-T shape makes the continuous line horizontal and yields overestimation of the horizontal.…”
Section: Resultsmentioning
confidence: 99%
“…Day and Avery linked the inverted-T illusion to bisection, since the divided line in the inverted T was judged as shorter than the continu" ous vertical segment. Bisection was pitted against radial-tangential effects in a study by Tedford and Tudor (1969). They reported that the illusion was altered by orientation when a 90°rotation made the continuous line segment horizontal rather than vertical.…”
mentioning
confidence: 99%